Piece-wise linear analog to digital (PLADC) converter process - Salami, Abdulazeez F.; Adetunji, Lawal Wahab; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)
Transducers are devices that transform energy from one form to another. Such transformation process may be applicable in the measurement of physical quantities, transfer of information and also in performing a certain control action. Transducers used as measuring devices are generally termed as sensors. Such transducers detect the changes in characteristics of a physical quantity and convert the change into a corresponding electrical signal. This is a common phenomenon when transducers are used to detect temperature, speed, force, liquid level or viscosity. On the other hand transducers, used to carry out control actions, are termed as actuators. These transducers usually convert an electrical signal into some form of physical control action such as heating or movement and are carried by the control devices. Various types of transducers exist meant for sensing and controlling different physical quantities. For example, a light dependent resistor (LOR) or a photodiode can be used to sense light intensity of an environment while lamps and LED displays can be used to control it. Likewise, a thermistor can be used to measure the temperature of an environment while a heater/fan can be used to control it and a tachometer can be used to measure the speed of a device while a stepper motor can be used to control it [1-3]. The focus of this chapter is on the problems and issues related to the interfacing of transducers when used as measuring devices or sensors in smart applications. Smart applications are also termed as tuned control for detecting changes in the parameter of interest which used to be ignorable in the traditional measurement and control systems